2012
DOI: 10.4049/jimmunol.1102840
|View full text |Cite
|
Sign up to set email alerts
|

STAT6-Dependent Regulation of Th9 Development

Abstract: T helper cell effector subsets develop in response to specific cytokine environments. The development of a particular cytokine-secreting pattern requires an integration of signals that may promote the development of opposing pathways. A recent example of this paradigm is the IL-9-secreting Th9 cell that develops in response to TGFβ and IL-4, cytokines that in isolation promote the development of iTregs and Th2 cells, respectively. To determine how the balance of these factors results in priming for IL-9 secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
235
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(249 citation statements)
references
References 39 publications
7
235
1
6
Order By: Relevance
“…Nonetheless, TGF-β/IL-15 had a more significant negative impact on TBX21 (T-bet) and EOMES gene expression and T-bet protein expression, which were both further down-regulated in the presence of CD28 costimulation (A/E beads). Such a negative effect of TGF-β on T-bet (34) might foster Th9 differentiation, because it also has been shown that T-bet counteracts the development of IL-9-secreting cells (35). Moreover, in response to TGF-β/IL-15, Vδ2 T cells up-regulated Eos and, in line with published data (23,24), FoxP3.…”
Section: Discussionsupporting
confidence: 75%
“…Nonetheless, TGF-β/IL-15 had a more significant negative impact on TBX21 (T-bet) and EOMES gene expression and T-bet protein expression, which were both further down-regulated in the presence of CD28 costimulation (A/E beads). Such a negative effect of TGF-β on T-bet (34) might foster Th9 differentiation, because it also has been shown that T-bet counteracts the development of IL-9-secreting cells (35). Moreover, in response to TGF-β/IL-15, Vδ2 T cells up-regulated Eos and, in line with published data (23,24), FoxP3.…”
Section: Discussionsupporting
confidence: 75%
“…Accordingly, the generation of Th9 cells was absent in STAT6-deficient and GATA3-deficient mice, which confirmed that STAT6 and GATA3 were essential in the generation of Th9 cells (9). However, some data demonstrate that GATA3 is not directly involved in the transcriptional regulation of the il9 gene, but acts rather as a molecule involved in the downregulation of Foxp3, a protein that could negatively affect Th9 development (21).…”
Section: Transcriptional Program Of Th9 Cellsmentioning
confidence: 66%
“…Moreover, the ectopic expression of Foxp3 reduces IL9 production by Th9 cells (21), thus demonstrating a negative effect of Foxp3 on Th9 differentiation. TGFb induces the activation of the SMAD pathway and the expression of PU.1, which could restrain Th2 polarization (22).…”
Section: Transcriptional Program Of Th9 Cellsmentioning
confidence: 99%
“…In general, selective cytokine receptor or SOCS protein expression serves as a major buffer to resist cytokine-driven repolarization of T cells, although DNA accessibility (discussed next) also has a crucial role. Second, the so-called 'master regulators' or 'lineage-defining' transcription factors T-bet, GATAbinding protein 3 (GATA3), RORγt, BCL-6 and FOXP3 have a substantial, but often incomplete, role in setting the transcriptional programmes of T H 1, T H 2, T H 17, T FH and T Reg cells, respectively 62,[113][114][115] . The capacity for these transcription factors to directly antagonize each other's functions through direct protein-protein interactions may impart coherency in effector responses 11,116 (FIG.…”
Section: Box 2 | Phenotypic Plasticity In Inflammatory and Regulatorymentioning
confidence: 99%